Konseling Remaja yang Kecanduan Gadget Melalui Terapi Kognitif Behavior - Firdaus, Wahyu; Marsudi, Muhammad Sholeh (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2021)
This paper aims to explain the counseling of adolescents who are addicted to gadgets through cognitive behavioral therapy. Teenagers who use gadgets are increasing. The impact of its use can be positive and negative. However, gadget addiction among teenagers has a negative impact so they tend to forget their learning task, forgetting basic needs such as eating, drinking, bathing, and having trouble sleeping. Certainly, teenagers who experience the negative impact of this gadget need to be treated with cognitive behavior therapy by a counselor. The method used in this paper is a qualitative description by analyzing the phenomenon of using gadget for adolescents. The approach used is a counseling approach with cognitive behavioral therapy theory. This article concludes that adolescents addicted to gadgets can be treated through cognitive behavioral counseling which refers to cognitive improvements that have detrimental effects both physically and psychologically. Though this therapy, those who are undergoing changes, cognitive, and emotional can control adolescents to control themselves.